“Worthy my blood”: Inheritance, Imitation, and Gendered Familial Emotions in John Marston’s Antonio Plays - Allen, Megan Elizabeth (Renaissance and Reformation / Renaissance et Réforme, 2014)
Examining the Antonio plays by John Marston, I argue that the metaphors used to portray familial emotions reveal the ideologies that underpin both excessive and normative versions of familial relationships; these metaphors reveal the pressures placed on family emotions by economic and political ideologies. While critics have traditionally read instances of family breakdown in plays as moments that violate kinship norms, I argue that such moments of violence are caused by ideologies associated with inheritance structures which underpin descriptions and experiences of normative familial emotions.